Providing specialized care to patients with a rupture of the distal tendon of the biceps brachii: diagnosis and treatment algorithm - A. E. Medvedchikov; E. A. Anastasieva; A. A. Korytkin; I. A. Kirilova (Acta Biomedica Scientifica, 2022)
Biceps brachii distal tendon injury is rare, 2.55–5.35 per 100,000. This nosological form did not have a gender modality and was previously found mainly in middle-aged men (46.3 y.o.). By 2022, this injury “rejuvenated” and began to occur more often, covering the categories of juniors and young athletes, whose professional activities have expanded significantly with the advent of new power disciplines, contact sports and popularization of bodybuilding. The authors note the negative impact of smoking and the use of anabolic steroids, statins and obesity on the incidence of these lesions. The maximum supination force in this type of injury is reduced by an average of 40 %, and the maximum flexion force is reduced by an average of 20 %. Considering the significance of functional disorders not only of the elbow joint, but also of motor patterns of the entire upper limb girdle for professional athletes, sports-organized people and people involved in the physical aspects of labor, surgical treatment is recommended. Nonsurgical treatment can be aimed at suppressing edema and inflammation, limiting early movements in the elbow joint and increasing secondary muscle tension, and it is suitable for patients with low functional demand, poor compliance and high risks of both surgical treatment and anesthesia care. That is, the choice of treatment tactics is still based, in addition to anatomical changes and on the “subjective” patient data, his/her needs for physical activity and requires an algorithmic approach in order to avoid both known complications and confidently predict a positive result during the prehospital period. Based on ten years of clinical and practical experience adjusted by widely available scientific periodicals, we have developed a scheme that is understandable to every specialist in the field of traumatology, orthopedics or sports medicine, and is applicable regardless of the medical institution level. For the first time, this scheme was published in this work.